A New Scoring System for the Assessment of Neonatal Abstinence Syndrome - Kocherlakota, Prabhakar; Qian, Edward C.; Patel, Vishwas C.; Mandru, Cosmina; Vilar, Rolando E.; Alpan, Gad; La Gamma, Edmund F. (American Journal of Perinatology, 2020)
Objective This study aimed to evaluate the concordance of a new scoring system for neonatal abstinence syndrome (NAS) and NAS scores to the traditional Modified Finnegan Neonatal Abstinence Scoring Tool (M-FNAST) score. The NAS score is based on the physiology of withdrawal, with equal emphasis on behavior, and neurological signs.Study Design The NAS scores for a control group of 202 healthy, term neonates were compared with those for 45 term neonates with NAS. The NAS and M-FNAST scores obtained simultaneously in 45 term neonates with NAS were compared using correlation, linear regression, and receiver operating characteristic curve analysis to determine the validity, reliability, and specificity of the NAS scores.Results The association between the NAS and M-FNAST scores was high (Spearman's correlation, 83%; linear regression, 83%), with an area under the curve of the NAS score of 1.00 (p < 0.01). A cut-off NAS score ≥4 identified NAS neonates with a sensitivity of 100% and specificity of 96%. The values of intraclass correlation, interrater agreement, and Cronbach's α were 0.63, 0.88, and 0.63, respectively.Conclusion The new NAS scoring system is valid, reliable, physiologically based, and correlates closely with the M-FNAST score. The NAS scores may require further validation before its use in clinical practice.
Keywords: neonatal abstinence syndrome; NAS scores; withdrawal; physiological